The Practice of Enterprise Modeling 9th IFIP WG 8.1. Working Conference, PoEM 2016, Skövde, Sweden, November 8-10, 2016, Proceedings - Horkoff, Jennifer; Jeusfeld, Manfred A.; Persson, Anne (Lecture Notes in Business Information Processing, 2016)
This volume constitutes the proceedings of the 9th IFIP WG 8.1 Conference on the Practice of Enterprise Modeling held in November 2016 in Skövde, Sweden. The PoEM conference series started in 2008 and aims to provide a forum sharing knowledge and experiences between the academic community and practitioners from industry and the public sector. The 18 full papers and 9 short papers accepted were carefully reviewed and selected from 54 submissions and cover topics related to information systems development, enterprise modeling, requirements engineering, and process management. In addition, the keynote by Robert Winter on "Establishing 'Architectural Thinking' in Organizations" is also included in this volume.